The role of confidence profiling in cognitive-behavioral interventions in sport - Hays, K.; Thomas, O.; Maynard, I. W.; Butt, J. (The Sport Psychologist, 2010)
This study examined the applicability of confidence profiling to the development of an individualized intervention designed in accordance with Murphy and Murphy`s (1992) eight step cognitive-behavioral model. The case study design illustrated the potential uses and benefits of confidence profiling when developing an athlete driven intervention to enhance the sport confidence of a female swimmer. Specifically, it showed how confidence profiling can act as an applied measure to accurately assess sport confidence from the athlete`s own perspective, provide the basis of an intervention targeted toward the athlete`s individual confidence needs, and provide feedback to the sport psychologist concerning the effectiveness of the intervention. A postintervention interview with the athlete highlighted the usefulness of the confidence profiling process. Specifically, the profiling process helped to raise the athlete`s awareness of the factors that facilitated and debilitated her sport confidence. Furthermore, the athlete reported feeling more confident and very satisfied with the mental skills training, which she perceived resulted in performance gains.